STUDI TINGKAT PENYALAHGUNAAN NARKOBA PADA MAHASISWA DI DENPASAR DAN BADUNG - Sugitha, Ni Putu Citra Anggryni; Wirajana, I Ngengah; Wirasuta, I Made Agus Gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
The level of knowledge and their abuses of drugs among students in some university in Denpasar and Badung regency have been assessed. Eight hundred students have been integrated on survey of knowledge-risk - effects survey and 2085 students were screened for drugs abused. Aim of this study was to assets the drugs knowledge level of students and determine their abuser level uncorrelated to their risk. We found out that, all students have ever attended sort course on drugs abuses and 85 % of student’s active searched drugs information through internet. On the contrary was obtained the low level (28-36%) of knowledge-risk-effect on drugs. About the 34% of 800 respondents presented high risk to abused drugs. Surprisingly it was found out just one among 2085 students positive consume codeine after screening and determinations tests.
Keywords: drugs abuse, students, drugs knowledge